Peran Ayah Sebagai Role Model Dalam Keluarga Menurut Perspektif Alquran: Pendidikan Keluarga Nabi Ibrahim AS - Riza Faisal Husaini (Fakultas Agama Islam Universitas Al Washliyah, 2025)
A father plays a crucial role as a role model in shaping the character and personality of children, as well as in creating a harmonious family environment. This paper examines the role of the father from the perspective of the Qur'an, emphasizing the importance of leadership, responsibility, and moral exemplarity. Through the family education of Prophet Ibrahim (AS), the article analyzes how Prophet Ibrahim (AS) demonstrated adherence to Allah (SWT), patience, justice, and compassion, which significantly shaped the values within his family. A descriptive-analytical approach is employed to analyze relevant Qur'anic verses and traditions. The findings of this study show that the Qur'an emphasizes the father's role not only as the provider but also as the primary spiritual and moral guide. The example set by Prophet Ibrahim (AS) provides practical guidance for modern fathers in fulfilling their roles as effective role models. The phenomenon of fatherlessness in Indonesia, such as children who lose their fathers due to death, divorce, or fathers who are emotionally absent because of being preoccupied with work, and the impact of patriarchal culture that traditionally divides caregiving roles, exacerbates this issue. This situation leads to psychological problems for children, such as confusion, and negative behaviors such as juvenile delinquency or involvement in harmful activities, including actions that violate social norms and laws, such as brawling, drug abuse, theft, promiscuity, smoking, and truancy. Such delinquency may arise from internal factors such as mental disorders and low self-esteem, as well as external factors such as peer influence and family environment. The impact can damage adolescents' mental health, education, and social relationships, even leading to serious legal issues. Prevention and intervention require the attention of parents, religious education, guidance at school, and counseling. Therefore, the presence of fathers in family education is essential, as exemplified by Prophet Ibrahim (AS) as the Founding Father, whose role can be emulated in family life.